1987
DOI: 10.1002/aoc.590010608
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tributyltin in estuarine sediments and oyster tissue, Crassostrea virginica

Abstract: An analytical method to determine tributyltin (TBT) in oyster tissue, Crassostvea virginica, and estuarine sediments is described. Recoveries of TBT from oysters range from 86 to 102% when samples are fortified at concentrations ranging from 22 to 890pgkg-' (wet weight); recoveries from sediment range from 92 to 105% for samples fortified from 20 to 500 pg kg -(dry weight).Feral oysters and natural sediments were analysed and shown to be contaminated with TBT. Oysters collected near a marina contained concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

1988
1988
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 3 publications
1
16
2
Order By: Relevance
“…The sediment can then become toxic to benthic organisms." Rice et al 33 have found TBT concentrations as high as 290 pg kg-' (dry weight) in Chesapeake Bay sediment.…”
Section: Effect On Benthosmentioning
confidence: 98%
See 3 more Smart Citations
“…The sediment can then become toxic to benthic organisms." Rice et al 33 have found TBT concentrations as high as 290 pg kg-' (dry weight) in Chesapeake Bay sediment.…”
Section: Effect On Benthosmentioning
confidence: 98%
“…33 In addition, they found that analyses of samples collected from contaminated and unpolluted sites indicated that the TBT is present in sediment and oysters at levels consistent with the boating activity. 33 TBT concentrations were measured in softshell clam (Mya arenaria) and American oyster (Crassostrea uirginica ) tissues from ten Maryland sites of the Chesapeake Bay by Unger et a1.& This study showed that the TBT concentrations in softshell clam tissues were related to seasonal climate changes. The lower concentration levels in the soft-shell clam tissue found during the winter months were attributed to a decrease in clam activity in low water temperatures, as well as to a decrease of TBTs in the water column, which coincided with a decrease in boating activity.…”
Section: Effect On Benthosmentioning
confidence: 99%
See 2 more Smart Citations
“…Amended diets were prepared on a weekly basis throughout the study. The levels of TBT and PCB-126 used in this study are based on the data of Rice et al (1987) that show sediment and oyster tissue burdens of TBT range between 1 and 1000 ppb in the Chesapeake Bay area. Coplanar PCBs have been detected at the parts per billion level in New Bedford Harbor, Lake Michigan, and the Hudson River (Pruell et al, 1988;Niimi & Oliver, 1989).…”
Section: Animals and Dosing Regimementioning
confidence: 99%